Commisioning Test of 3 x 3kW Solar Power Plants for Laboratory Purpose - Yunus, A.M Shiddiq; Hamzah, Nur; Mulyadi, Musrady; Firman, Firman; Yunus, Muhammad Yusuf; Marhatang, Marhatang; Bhuana, Chandra; Klistafani, Yiyin (Politeknik Negeri Ujung Pandang, 2023)
A laboratory is an important part in the learning and teaching process, therefore, it is necessary to improve both in terms of equipment and laboratory management standards. State Polytechnic of Ujung Pandang has carried out the design process for a solar power plant (SPP) system with a capacity of 3 x 3 kW to support the learning process related to alternative and renewable energy lectures and practicum. One part of the procedure for activating newly installed laboratory equipment is the commissioning test. From the commissioning results, the results show that 3 x 300 Wp and independent 375 Wp SPP can work well with an average DC voltage rating of 80 V and for AC loads with an average voltage of 220 V. All types of loads, both AC and DC can work properly after going through the DC Couple and AC Couple with the inverter.